Free control of filaments rotating induced by vortex femtosecond laser beams interference in fused silica. (June 2022) - Li, Dongwei; Chang, Junwei; Xu, Litong; Zhang, Lanzhi; Xi, Tingting; Hao, Zuoqiang
Highlights: Controllable annular multiple filaments are obtained in fused silica by using two collinear interfered femtosecond vortex laser beams with high power. The pattern, number and rotation of the filaments can be well controlled with the topological charges and delay time of two laser beams. It is the first time, to the best of our knowledge, to realize the continuous rotation of the annular filaments through the exterior regulation. The work provides a convenient and flexible method to control the rotation of annular filaments, and will promote further studies on the related applications which require the regular annularly distributed filaments, such as laser micro-machining, microwave guiding, annular photonic lattice generation, and so on. Abstract: Controllable annular multiple filaments (MF) are obtained in fused silica by using two collinear interfered femtosecond vortex laser beams. Both the distribution and number of filaments which are generated from the petaloid interference pattern, can be well controlled with the topological charges of input beams. More interestingly, we find that the MF pattern can be continuously rotated by changing the phase difference between the two interfered beams. This paper provides an effective way to generate annular MF with stable distribution, and a flexible method to control the rotating filamentation pattern through exterior regulation.